APPLICATION OF HYDROPHYILIC INTERACTIONS LIQUID CHROMATOGRAPHY FOR PARABENS ANALYSIS - A. S. Osipov; O. A. Popova; A. I. Sulimenkova; M. V. Nezdolieva (Разработка и регистрация лекарственных средств, 2019)
There are results of the possibility of applying a chromatographic column Zorbax NH2 150х4,6 mm (5 µm) to separate the esters of 4-hydroxybenzoic acid (parabens). Separation of test compounds on the column with aminosorbents in hydrophilic interaction chromatography is possible at a content of more than 95% of acetonitrile in the mobile phase. The resolution between peaks of parabens in a hydrophilic interaction liquid chromatography is substantially less than in a reverse-phase chromatography. In contrast to the amino nitrile groups Zorbax XDB CN columns practically haven’t affinity for the phenolic hydroxyl groups of parabens in a hydrophilic interaction liquid chromatography. Chromatography column Zorbax NH2 can be used to detect a normalized impurity in paraben - 4-hydroxybenzoic acid [mobile phase: acetonitrile - 1% acetic acid in water (80:20)].